Rigid-foldable cylindrical origami with tunable mechanical behaviors - Fengrui Liu; Tatsuro Terakawa; Siying Long; Masaharu Komori (Scientific Reports, 2024)
Abstract Rigid-foldable origami shows significant promise in advanced engineering applications including deployable structures, aerospace engineering, and robotics. It undergoes deformation solely at the creases during the folding process while maintaining rigidity throughout all facets. However, most types of cylindrical origami, such as Kresling origami, water-bomb origami, and twisted tower origami, lack rigid-foldability. Although shape transformation can be achieved through elastic folding, their limited rigid foldability constrains their engineering applications. To address this limitation, we proposed a type of cylindrical origami inspired by Kresling origami, named foldable prism origami (FP-ori), in this paper. FP-ori possesses not only rigid-foldability but also several tunable properties, including flat-foldability, self-locking, and bistability. The geometric properties of FP-ori were analyzed and the relationship between different parameters and tunable mechanical behaviors were verified through finite element method simulations, as well as experiments using paper models. Furthermore, we proposed stacked structures composed of multiple cubic FP-ori units, the rotation directions of which could be controlled through the combination arrangement. And drawing inspiration from kirigami, a negative Poisson’s ratio tessellation structure was created. These results indicated that FP-ori has substantial potential for broad application in engineering fields.